Bioelectromagnetics Current Concepts The Mechanisms of the Biological Effect of Extremely High Power Pulses - Ayrapetyan, Sinerik N.; Markov, Marko S. (Nato Security through Science Series B:, Physics and Biophysics,, 2006)
This volume includes the lectures and selected posters on different aspects of biological effects of EMF, presented at the NATO ADVANCED RESEARCH WORKSHOP "The mechanisms of biological effect Extremely High Power Pulses (EHPP)" (3-5 March 2005) and the UNESCO/WHO/IUPAB Seminar "Molecular and Cellular Mechanisms of Biological Effects of EMF" (1-2 March 2005) that took place in Yerevan, Armenia. The gracious support of several international organizations made possible to bring together 47 scientists, engineers, physicians and policy makers from 21 countries from Europe, North and South America, Asia. The Capital of Armenia, Yerevan, provided an excellent opportunity for discussions of the experimental data and theoretical models of EMF effect on various levels, starting from cell aqua bathing medium to the whole organism, including the human, applying multidisciplinary approaches. The continuous increase of the number of man made EMF sources leads to dramatic changes in the spectrum of EMF in the biosphere. During the last two decades the public concern about potential hazard of EMF generated by power and distribution lines, as well as mobile communications and base stations have initiated serious public concern and has triggered the attention of the WHO, which reflected in the EMF project of harmonization of standards. At the same time, contemporary medicine largely uses EMF diagnostic methods. The beneficial effects of EMF are complemented with a large scale of EMF therapeutic modalities used in a number of countries, helping millions of people.